Serum albumin polymorphism and certain production traits in indigenous ducks of Kerala * - Mahanta, J D; Ramakrishnan, A; Jalaudeen, A (The Indian Journal of Animal Sciences, 2012)
Indigenous ducks, viz. Chara, Chemballi (300 samples) of Kerala were typed for serum Alb polymorphism and 3 clear phenotypes (AA, BB and AB) were observed. The frequency of homozygous Alb-AA phenotype was higher in Chemballi (52.67%) than Chara (44.00%). Association studies indicated significant influence of Alb phenotypes and age at first egg, production, egg weight and body weight in both Chara and Chemballi ducks.